Job and career satisfaction in an austerity environment: the role of job security and passion towards work. (2017) - Papadimitriou, Dimitra; Winand, Mathieu; Anagnostopoulos, Christos
This study investigates the role of passion in forming job and career satisfaction among employees in the sport industry using the dualistic model of passion developed by Vallerand et al. (2003). The research was conducted within a context of austerity measures and aimed to examine the mediating effects of job security in the relationship between passion and satisfaction at work. Employees within Greek municipal sport organisations completed a self-administered questionnaire (N = 170) in order to measure their level of passion towards their work (both harmonious and obsessive), their job and career satisfaction, and their perceptions of job security. Data were treated with confirmatory factor analysis (CFA) and multiple regression analyses using SPSS and Amos 21.0. The findings reveal that harmonious passion is significantly positively related to both job and career satisfaction, and that job security mediates these relationships. The research demonstrates the benefits of having harmoniously passionate employees, as well as the importance of strengthening or retaining feelings of job security under drastic socio-economic measures.